Development and water requirements of cowpea under climate change conditions in the Brazilian semi-arid region - Edmilson G. Cavalcante Junior; José F. de Medeiros; José Espínola Sobrinho; Vladimir B. Figueirêdo; João P. N. da Costa; Wesley de O. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to determine the impacts that climate change may cause on the development and evapotranspiration of cowpea, in semi-arid climate region of Northeast Brazil. The study was conducted in the municipalities of Apodi, Ipanguaçu and Mossoró, in the state of Rio Grande do Norte. In order to evaluate the influence of climate change on crop water consumption, changes in air temperature and relative humidity were simulated using the PRECIS climate model. Two scenarios of emissions were evaluated based on the report of the Intergovernmental Panel on Climate Change: a pessimistic named A2 and an optimistic B2. The duration of the crop cycle showed an average reduction of 14 and 23 days for the optimistic and pessimistic scenarios, respectively. Temperatures will be well above the limit tolerated by crop, which could have a negative impact on its development and yield. There will be a decrease in total evapotranspiration of 4.8%, considering the optimistic scenario, and 8.7% in the pessimistic scenario.